STRATEGI MEDIA START UP DALAM PEMANFAATAN TEKNOLOGI BERBASIS IOT (INTERNET OF THINGS) SEBAGAI MEDIA PROMOSI BISNIS - Ahmad Budi Sulistioyuwono, S.E, M.M, Ahmad Budi Sulistioyuwono, S.E, M.M (Profilm Jurnal Ilmiah Ilmu Perfilman dan Pertelevisian, 2022)
Its media start-up strategy is important to pay close attention to the sustainability of the company. The selection of the right and effective strategy is able to support the promotion of business carried out by the company to achieve its vision and mission. The development of internet of things (IoT)-based technology is rapidly accelerating in the digital world, which can bring abundant benefits. Media start-ups certainly see this gap as a lucrative business promotion medium. In addition to making, it easier in the field of promotion, the price offered is also cheaper and can reach all corners. This study was conducted with a descriptive qualitative method in the form of literature studies obtained from journals and scientific articles. The results obtained show the right and effective strategy by observing the prevailing digital trends, knowing the success rate of digital marketing campaigns, and preparing a business promotion plan.